2020
DOI: 10.1073/pnas.1919972117
|View full text |Cite
|
Sign up to set email alerts
|

Early investments in state capacity promote persistently higher levels of social capital

Abstract: Social capital has been shown to positively influence a multitude of economic, political, and social outcomes. Yet the factors that affect long-run social capital formation remain poorly understood. Recent evidence suggests that early state formation, especially investments in state capacity, are positively associated with higher levels of contemporary social capital and other prosocial attitudes. The channels by which early state capacity leads to greater social capital over time are even less understood. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In the end, what best explains the general picture? Considering all findings, we suggest that SoMi may be conceptualized as a specific and effective expression of social capital ( 47 50 ), a comprehensive perspective on society with important implications for its development and functioning ( 30 ). Following one of the definitions, the economic function of social capital is to diminish the costs of formal coordination tasks by using informal social communication channels ( 51 ).…”
Section: Discussionmentioning
confidence: 87%
“…In the end, what best explains the general picture? Considering all findings, we suggest that SoMi may be conceptualized as a specific and effective expression of social capital ( 47 50 ), a comprehensive perspective on society with important implications for its development and functioning ( 30 ). Following one of the definitions, the economic function of social capital is to diminish the costs of formal coordination tasks by using informal social communication channels ( 51 ).…”
Section: Discussionmentioning
confidence: 87%
“…Finally, our analysis contributes to recent work that has shown that other state investments in the Early Republic in the United States, particularly the postal system, are predictive of later positive outcomes regarding economic innovation (Acemoglu, Moscona, and Robinson 2016; Rogowski et al 2021) and social capital (Jensen and Ramey 2020). Our results complement these studies and extend them by examining a different type of state investment—education, focusing on a range of outcomes and taking advantage of a natural experiment for causal inference.…”
Section: Introductionmentioning
confidence: 60%
“…The spatial layout of the city, the concentrated settlement pattern of residential terraces, roads that connected neighborhoods, water dispersal features, marketplaces, monumental public/ritual buildings, and greater defensive security all facilitated production, distribution, and consumption shifts that yielded the opportunity for enhanced well-being. These early infrastructural investments at Monte Albán also likely undergirded Monte Albán's sustainability in a manner that parallels more contemporary examples (e.g., Amin, 2008;Klinenberg, 2019;Latham and Layton, 2019;Jensen and Ramey, 2020). Although growth slowed after the first 300 years of occupation, Monte Albán remained the preeminent regional central place in the Valley of Oaxaca for 1,300 years.…”
Section: Joint Production Coactive Processes and New Institutionsmentioning
confidence: 74%
“…What makes Monte Albán's foundational episode all the more important to continue to study is that it appears to have led to a sustainable central place with a relatively low level of inequality and better degree of wellness (health/diet) compared to many of its contemporary (prehispanic) Mesoamerican urban centers. In short, this is a premodern historical instance where early investments in public infrastructure and goods fostered longer-term sustainability (Jensen and Ramey, 2020).…”
Section: Discussionmentioning
confidence: 99%